PENERAPAN PEMBELAJARAN “WISATA LOKAL” MELALUI WEB SEBAGAI UPAYA PENINGKATAN RESPON DAN HASIL BELAJAR MATEMATIKA SISWA DI SMKN 1 SUMBERREJO - Sriatun Sriatun (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Education Unit Level Curriculum requires students to be active and cooperate with other students, in the implementation of learning indicate the existence ofdeficiency, One of them still rarely asks students, and if asked by the teacherlooks student hesitate and afraid to reply.In addition in the end hours studentsfeel lazy in follow teaching and learning activities. This study aims to improvestudent responses and mathematics learning outcomes on statistical materials.This type of research is a classroom action research. The research wasconducted in class XII of SMKN 1 Sumberrejo-Bojonegoro. Student responsedata obtained from the observation and recording of handycam at the time ofstudent group discussion of learning result data obtained from post testassessment.Keywords: Learning "Local Tour" web, student responses, mathematics learning outcomes.